Case Report: An Unusual Case of Biventricular Thrombosis in a COVID-19 Patient With Ischemic Dilated Cardiomyopathy: Assessment of Mass Mobility and Embolic Risk by Tissue Doppler Imaging - Sonaglioni, Andrea; Albini, Adriana; Nicolosi, Gian Luigi; Rigamonti, Elisabetta; Noonan, Douglas M.; Lombardo, Michele (Frontiers in Cardiovascular Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein binds to angiotensin-converting enzyme 2 (ACE2) receptor on vascular cells. As a consequence, patients with COVID-19 have an increased incidence of thromboembolic complications of the SARS-CoV-2 infection and subsequent endothelial cell damage with consequence of development systemic vasculitis and diffuse intravascular coagulation. The present case describes a COVID-19 patient with ischemic dilated cardiomyopathy, who presented with congestive heart failure and echocardiographic evidence of biventricular apical thrombi. The peak antegrade longitudinal velocity (Va) of each thrombotic mass was measured by pulsed wave tissue Doppler imaging (PW-TDI). Both left ventricular and right ventricular apical thrombi were found with a TDI-derived mass peak Va <10 cm/sec. There was no clinical evidence of neither systemic nor pulmonary embolization, probably due to the hypomobility of both left and right ventricular masses.